2013 IEEE International Conference on Image Processing 2013
DOI: 10.1109/icip.2013.6738259
|View full text |Cite
|
Sign up to set email alerts
|

A combined active contours method for segmentation using localization and multiresolution

Abstract: Image segmentation is a fundamental step in many image processing applications. To achieve high-quality segmentations active contours are commonly used. However, state of art strategies are not able to provide successful results in all the conditions. Additionally, the strategies that get the best overall results are computationally expensive and need to manually set some parameters, which decreases their usability.Here, we propose a novel active contours-based segmentation method that, through the combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Yanez et al [16] showed that using an adaptive radius drastically decreases the computational efficiency while only slightly increasing the quality of the results. For this reason, we use a fixed localisation radius (i.e.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Yanez et al [16] showed that using an adaptive radius drastically decreases the computational efficiency while only slightly increasing the quality of the results. For this reason, we use a fixed localisation radius (i.e.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Active contours are a very powerful tool for detecting contours, especially if we have an initial approximation of the contour that we want to reach. Therefore, to facilitate the labeling task, we have included in TSLAB the active contour-based segmentation strategy proposed in [ 33 ].…”
Section: Active Contours Toolmentioning
confidence: 99%